Procedures and tools for generating and selecting alternatives in LCA. - Bras-Klapwijk, Remke M. (The International Journal of Life Cycle Assessment)
Life Cycle Assessments (LCAs) frequently do not contribute to sustainable development because product alternatives with a truly low environmental burden are not included in the assessment. As a result, environmentally friendly alternatives are not uncovered, although much effort has been put into collecting inventory data and making an impact assessment. Part of this problem is caused by the defensive use of LCAs. Companies eager to show that their product is not too bad for the environment prefer to compare their product with alternatives that are not very promising in an environmental sense. To (mis) use LCAs in this way is quite easy, because the LCA methodology and handbooks provide few guidelines and little advice on how to generate and select adequate alternatives. An analysis of the problems related to the alternatives is given using insights drawn from the field of policy analysis-a field in which methodological rules for the generation of alternatives in policy studies have been developed-ecodesign and the LCA discipline and measures to reduce the problems are developed. Explicating the different steps in the determination of alternatives in the goal and scope formulation stage of an LCA process and the development of a toolbox for this activity, would certainly improve the quality of the selection of alternatives. Furthermore, involving stakeholders and a group of experts in the generation and selection process will increase the variety and relevance of alternatives, and the social support for alternatives.